EVALUATION AND EXPLORATION OF MANAGEMENT CONTROL SYSTEMS IN VILLAGE OWNED ENTERPRISES - Azhari, Intan Putri; Bustamin, Bustamin (Universitas Brawijaya, Indonesia, 2022)
Village-Owned Enterprises (BUMDes) Panggung Lestari is one of the reference BUMDes in Indonesia as it has run multiple business units and has successfully contributed significant Village Original Income (PADes) to the village. The research goal is to evaluate and provide solutions for implementing MCS in Panggung Lestari. Qualitative descriptive research method and case study approach by collecting data through observation, in-depth interviews, and documentation review. Then perform data triangulation so that the data can be interpreted and closed. The results showed that Panggung Lestari was regulated by Village Regulation No. 9 of 2016 and AD/ART. However, BUMDes Panggung Lestari did not have detailed operations guidelines, such as standard operating procedures and job descriptions. Panggung Lestari also did not yet have strategic planning and budgeting. Â Corporate level performance measurement is regulated from the top down but has not been well documented. While measuring performance at the business unit level, only the KUPAS Business Unit has performance measurement parameters for employees, while other business units do not yet have performance measurement parameters. Performance incentives are given in financial form but for employees who did not have a good system. The bottom line is that the BUMDes don't have a good MCS yet, so management needs improvement.